Do Neurodegenerative Diseases Affect Creativity? Divergent Thinking in Frontotemporal Dementia and Parkinson's Disease. Issue 1 (2nd January 2019) - Ruggiero, F.; Cortese, F.; Lavazza, A.; D'Urso, G.; Di Nuzzo, C.; Marceglia, S.; Pravettoni, G; Priori, A.; Ferrucci, R.
Abstract : Creativity is considered to be one of the most important characteristics that humans possess. It emerges from fundamental cognitive operations and the activation of specific brain regions. In several neurological disorders, such as frontotemporal dementia (FTD) and Parkinson's disease (PD), creativity plays an important role in diagnosis and rehabilitation strategies. This study examined the link between creativity and pathology in a sample of neurological patients (idiopathic PD, n = 17; FTD, n = 11 with behavioural or semantic variants), and 15 healthy subjects (Mini Mental State Examination score ≥ 20; age range, 45 to 85 years) using the Divergent Thinking Test. The FTD group exhibited lower scores than the PD and control groups. Furthermore, PD patients performed significantly better on the single DTT factor, originality, than controls. These results are discussed in relation to neurological mechanisms that may influence creative strategies in dementia. Finally, it has been proposed creativity therapy as a cognitive rehabilitation approach, which may help patients enhance and maintain cognitive functions, reduce the severity of emotional disorders, and promote social interactions.